The AVOID Plan: Model of Success to Limit Electronic Vaping Rates on a College Campus - Kessler, Theresa A.; Rayman, Lynette (British Journal of Healthcare and Medical Research, 2023)
Background: College students are a demographic group in which vaping is especially prevalent. National experts recommend promoting awareness of e-cigarette harm, implementing evidence-based prevention and treatment activities, and promoting tobacco free campus policies. Methods: A student-faculty collaborative research team initiated the Anti-Vaping Ongoing Information Dissemination (AVOID) plan based on best evidence and the results of a pre-implementation survey. The pre- and post-implementation surveys were distributed to random, stratified samples and assessed demographic information, vaping behaviors, and intentions for behavior change. A multicomponent, tailored intervention was created. Strategies with cessation and Quitline information included social media posts on Instagram; tabling displays in campus buildings; public service announcements, distribution of educational materials, and stress balls at sporting events; campus TV messages; coverage of issues related to vaping in the university student newspaper; a YouTube video; and educational posters/pamphlets displayed in campus buildings. Results: Post-implementation, all students (n = 487) reported seeing at least one AVOID strategy, with posters (74.3%, n = 345) as the most viewed followed by social media posts (40.5%, n = 188). Reported intentions to quit according to the Transtheoretical Model stages of change was significantly different following the multicomponent educational strategies (X2(5) = 26.408, p < .001), with 61.5% planning to quit within the next 6 months compared to 33.3% pre-implementation. Conclusions: Collaborative educational initiatives such as the AVOID program should continue on college campuses. Campus representatives should inform college students who vape and those who might begin the behavior about the negative effects of vaping.